CITRA PEREMPUAN DALAM PUISI “JERITAN PEREMPUAN YANG MELAWAN” KARYA NOLINIA ZEGA - Kamila, Ana Tasya; Adawiyah, Siti; Julianto, Indra Rasyid (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2025)
This research aims to foster awareness of the deep meaning contained in the poem "Jeritan Perempuan yang Melawan" by Nolinia Zega regarding the figure of women portrayed in physical, psychological, and social aspects. The research method used is qualitative descriptive with heuristic and hermeneutic techniques to focus the analysis on the image of women. The results of this study show that the image of women described in this poem can be seen from three aspects, namely physical, psychological, and social aspects. In the physical aspect, women are always reviewed from their appearance set by society. On the psychological aspect, women often feel depressed and unhappy due to the demands of life that are not in accordance with their desires. In the social aspect, women are portrayed as always bound by norms and stigmas that require them to fulfill certain roles.